Bartók and the German Music Tradition – Heritage and Impact - Hohmaier, Simone (Danish Yearbook of Musicology, 2005)
After a short review of concepts about national and German music, which concentrates upon Dahlhaus’ ideas and Sponheuer’s formation of two idealtypes, the article deals with Bartók’s understanding of German music and with the impact of representative German composers like Bach, Beethoven and the so-called ‘Neudeutsche Schule’ on Bartók’s music. In Bartók’s own understanding of German music historically grown ideas, especially the binary stereotypes by Sponheuer reappear, as can be deduced from his writings. Regarding Bartók’s influence on the German musical scene after World War II, the article at first recalls the supposed insignificance of Bartók’s compositional concepts for young German composers of that time and then names several trends to be observed nevertheless: composers pay attention to Bartók’s pedagogical compositions, to his exploitation of folk music and shares the opinion of Bartók as a worthy successor to Beethoven. It presents compositions by Kurt Schwaen, Helmut Bornefeld, and Michael Denhoff, as examples for the diverse field of the productive reception of Bartók’s works on the German contemporary music scene.